Teachers’ challenges, capabilities, and needs in teaching learners with reading difficulties - Leylanie Adao; Cesar Chester Relleve; Joel Salazar; Katrezia Fiel Macawile; Marites Chavez (CV Rezki Media, 2023)
This study aims to understand the teachers’ challenges, capabilities, and resources in teaching learners with reading difficulties. It utilized a qualitative descriptive approach and data were collected using single focus group discussion. A descriptive thematic approach was employed following the method of Braun & Clark to analyze the data and describe the experiences of the informants. Participants of this study are 17 teachers from Junior High School in one public school in the City Schools Division of Dasmariñas who encountered students with reading difficulties in the conduct of their classes during the first quarter of school year 2022-2023. Findings revealed that in terms of challenges, the following themes emerged 1) Low participation in class, 2) Unmet learning competencies; as regards to capabilities 3) Language teachers are capable, 4) Content teachers have inadequate skills, and when it comes to teachers’ needs 5) Capacity building, 6) Intensification of reading intervention, and 7) Learning resources for reading.